Ab Initio Investigation of 1T-HfTe2 Monolayer for Adsorption of SF6 Decomposition Gases - Oli, Prabhakar; Chettri, Bibek; Adhikari, Rajendra Prasad; Adhikari, Devendra; Sharma, Bikash; Yadav, Shashit (Journal of Institute of Science and Technology, 2025)
In this study, the adsorption properties of three byproducts of sulfur hexafluoride (SF6) decomposition gases on a 1T-HfTe2 monolayer were investigated within the framework of Density Functional Theory (DFT). SF6 is commonly used in high-voltage transformers as an arc-extinguishing and insulating medium. The Perdew–Burke–Ernzerhof (PBE) functional within the Generalized Gradient Approximation (GGA) was employed for the computational analysis. Adsorption energy ( ), charge transfer ( ), band gap, density of states (DOS), and recovery time ( ) were calculated to understand the adsorption mechanisms of HfTe2 monolayers toward SF6 decomposition products. The results revealed that the adsorption of SOF2, SO2, and SO2F2 exhibits chemisorption, with adsorption energies of –0.41, –0.39, and –0.30 eV, respectively. Among these, SOF2 showed the strongest interaction, while SO2F2 exhibited the weakest. The HfTe2 monolayer demonstrated favorable and rapid recovery times, calculated to be 0.14 µs for SOF2 and 4 µs for SO2. These findings provide a foundation for the development of 1T-HfTe2-based sensors and adsorbents for use in SF6-insulated electrical equipment.